A review on carbon quantum dots: Synthesis, photoluminescence mechanisms and applications. (16th August 2022) - Zhang, Likang; Yang, Xue; Yin, Zhifu; Sun, Linlin
Abstract: Carbon quantum dots (CQDs), having outstanding biocompatibility, attractive catalytic performance, excellent optical properties, and valuable environment friendliness, are emerging as a new paradigm to design luminescent devices and show great potential in application fields such as biomedical sensors, optical and photonic devices. Furthermore, CQDs are known as one of the most promising carbon‐based nanomaterials in the 21st century. Therefore, they have attracted a lot of attention since they were first discovered in 2004. In this review, we explain the accepted photoluminescence mechanism of CQDs, including fluorescence and phosphorescence. There are two main types of synthesis strategies: top‐down approach and bottom‐up approach. At the same time, the main application fields, including ion detection, anti‐counterfeiting, biological imaging, food safety, sensors, lubrication additives, are reviewed. Finally, the existing bottlenecks, pending problems and prospects for the future of CQDs are discussed. Abstract : Carbon quantum dots (CQDs) have excellent optical properties, extraordinary biocompatibility, low toxicity, environmental friendliness, attractive catalytic performance, ultra‐small size, low cost, high chemical stability and easy functionalization. In this review, the synthesis strategy, photoluminescence mechanism and applications of CQDs are reviewed systematically.